Penggunaan Tanaman Lokal di Kampung Budaya Legok Hayam Desa Girimekar Kecamatan Cilengkrang Kabupaten Bandung untuk Kebutuhan Adat Tali Paranti - Nathania Rahadatul ‘Aisy; Tri Cahyanto (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The Use of Local Plants in Legok Hayam Cultural Village, Girimekar Village, Cilengkrang District, Bandung Regency for Tali Paranti Traditional Needs. This research aims to explore the community’s knowledge about the use of plants for Tali Paranti traditional activities. Data was collected through open interviews by visiting informants and closed surveys, including the distribution of questionnaires via Google Forms to reach all informants. The results of the study show that Coconut received the highest use value of 0.25, and the Fidelity Level was 25%. Through both qualitative and quantitative methods, this research provides insights into the interaction between the community and plants in the context of local culture.